Thermal Conduction in Metals: Mental Representations in 5-6 Years Old Children’s Thinking - Κaliampos, George; Ravanis, Konstantinos (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2019)
In this paper, we present the findings of research on mental representations of thermal conduction on the metal of children aged 5-6 years. The research was carried out using interviews of 87 urban area kindergarten students in Greece. The children were asked for predictions and macroscopic descriptions of phenomena illustrated in 3 different tasks during which simple thermal conduction experiments were performed with both daily and non-daily materials. The research results clearly show the vast majority of children express mental representations which are far from the scientific models used in education. Moreover, many children can make predictions on heat conduction without being able to analyze their way of thinking. Finally, differences were found in heat conduction on familiar and non-familiar materials used by children. Findings of the current research study are likely to equip teachers with the appropriate basic tools for designing their teaching interventions in the lessons of heat and thermal conduction for children aged 5-6 years.